Dampak penggunaan media sosial dalam pembelajaran: Perspektif dari berbagai studi kasus literatur - Hasnah, Nur (Maliki Interdisciplinary Journal, 2023)
Social media is a tool used by everyone as a tool to interact with one another online. Learning media is a tool that is used as a tool in the learning process. The use of social media in learning has positive and negative impacts. Excessive use of sisal media will have a negative impact on its users.